The effect of melatonin applications on offspring in experimentally induced uterine torsion in pregnant rats - Risvanli, A.; Saat, N.; Timurkaan, N.; Dogan, H.; Sahna, E.; Seker, I. (Wiley, 2018)
[Abstract Not Available]
22nd Annual Conference of the European-Society-for-Domestic-Animal-Reproduction (ESDAR) -- SEP 27-29, 2018 -- Cordoba, SPAIN